2019
DOI: 10.3892/etm.2019.8086
|View full text |Cite
|
Sign up to set email alerts
|

Meta‑analysis of the association between aldose reductase gene (CA)n microsatellite variants and risk of diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is one of the most severe microvascular complications of diabetes mellitus (DM). The (CA)n microsatellite variation of the aldose reductase (ALR) gene has been indicated to be associated with DR in previous studies; however, the results were inconclusive. To provide a more precise evaluation of the association between the (CA)n variations of ALR and the risk for DR, a meta-analysis was performed in the present study. Relevant articles were retrieved from the PubMed, Embase, Chinese Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…These allelic polymorphisms have been hypothesized to alter ALR2 mRNA levels and hence enzyme activity, thus contributing to diabetic microvascular complications [ 56 ]. However, to date, conflicting evidence has been presented; some studies have reported an association between the Z-2 allele and DR risk [ 57 , 58 ], whereas others have reported no association [ 54 , 55 ]. In a meta-analysis by Mi et al [ 57 ], comprising 17 studies, the Z-2 allele was reported as a risk polymorphism for DR in both Asian and Caucasian T1 and T2DM cohorts.…”
Section: Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…These allelic polymorphisms have been hypothesized to alter ALR2 mRNA levels and hence enzyme activity, thus contributing to diabetic microvascular complications [ 56 ]. However, to date, conflicting evidence has been presented; some studies have reported an association between the Z-2 allele and DR risk [ 57 , 58 ], whereas others have reported no association [ 54 , 55 ]. In a meta-analysis by Mi et al [ 57 ], comprising 17 studies, the Z-2 allele was reported as a risk polymorphism for DR in both Asian and Caucasian T1 and T2DM cohorts.…”
Section: Candidate Genesmentioning
confidence: 99%
“…However, to date, conflicting evidence has been presented; some studies have reported an association between the Z-2 allele and DR risk [ 57 , 58 ], whereas others have reported no association [ 54 , 55 ]. In a meta-analysis by Mi et al [ 57 ], comprising 17 studies, the Z-2 allele was reported as a risk polymorphism for DR in both Asian and Caucasian T1 and T2DM cohorts. Notably, only one study by Kumaramanickavel et al [ 59 ] has explored the association between the ALR2 dinucleotide repeat and DME risk.…”
Section: Candidate Genesmentioning
confidence: 99%
“…Some studies have suggested that the z-2 allele is associated with increased ALR activity [67] and DR pathogenesis in both T2D (stronger association) and T1D (weaker association) patients [50,53,68,69]. Two large meta-analyses have confirmed these findings, and both additionally found that the z+2 allele may be significantly protective against DR development in T2D [26,70]. Notably, however, found no significant association between any (CA)n allele and T2D once established risk factors were controlled for [30], suggesting that the (CA)n microsatellite may be only secondarily associated with DR through other clinical risk factors, rather than playing a primary role in its pathogenesis.…”
Section: Genetic Studies 41 Candidate Gene Studiesmentioning
confidence: 89%
“…Insulin resistance (IR) and impaired islet cell functions are characterized by an increase in glycemia, lipid metabolism disorders, and systemic inflammation that can lead to a variety of serious complications ( 1 ). According to the World Health Organization, diabetes is one of the diseases with the most known complications ( 2 , 3 ). Long-term increases in blood glucose are accompanied by large blood vessels and microvascular damage, putting the heart, brain, kidneys, peripheral nerves, eyes, feet, and other organs at risk.…”
Section: Introductionmentioning
confidence: 99%
“…complications (1). According to the World Health Organization, diabetes is one of the diseases with the most known complications (2,3). Long-term increases in blood glucose are accompanied by large blood vessels and microvascular damage, putting the heart, brain, kidneys, peripheral nerves, eyes, feet, and other organs at risk.…”
mentioning
confidence: 99%